Non-Linear Dynamic Analysis of Timber Frame Structure with Bolted-Fastener Connections - Thomas Catterou; Yann Sousseau; Sidi Mohammed Elachachi; Myriam Chaplain; Carole Faye (Vibration)
Understanding the dynamics of timber structures is essential for the timber structural engineering field, where it is necessary to build predictive numerical models and digital twins. Three similar-sized representative post-beam bracing frames with wood–metal assemblies were tested. Experimental modal analysis gave some indication of the non-linear behaviour of the structure. Then, the frame was submitted to a logarithmic sine sweep, which highlighted some specificities of the non-linear modes: dependence on the sweep direction and amplitude, jump, etc. These phenomena can be explained by friction and shocks in the assemblies. An accurate model of these non-linearities could lead to resilient and more earthquake-resistant timber structures, as the equivalent damping of a non-linear structure is way lower than for a linear one.